Accumulation and export of nutrients in harvested wood of Vochysia guatemalensis in small-scale forest plantations - Camacho Umaña, Manuel Ernesto (2017)
To enhance knowledge required for better management of tropical forest plantations, aboveground accumulation in different tree tissues (stem, branches, foliage and total) at different growth stages of guatemalensis (white yemeri) was studied. False time series were used from 16 small farmer sites in humid lowlands of Costa Rica. A 17-year-old stand with density of 483 trees ha"1 and 35 cm diameter at breast height accumulated 818 kg ha1 N, 686 kg ha1 K, 552 kg ha1 Ca, 284 kg ha1 Mg, 1 14 kg ha1 P, 152 kg ha1 S, Fe, 101 kg ha"1 Mn, 0.5 kg ha"1 Cu, 2 kg ha"1 Zn, 1 kg ha"1 B and 1063 kg ha"1 Al. The expected nutrient timber harvest (stem) was 499 kg ha"1 N, 485 kg ha"1 K, 314 kg ha"1 Ca, 188 kg ha"1 Mg, 46 kg ha"1 P, 69 8 kg ha1 Fe, 29 kg ha"1 Mn, 0.5 kg ha"1 Cu, 1.4 Zn, 0.6 kg ha"1 B and 783 kg ha"1 Al. Aluminium accumulation was higher than other nutrients, confirming that V. guatemalensis is an Al-hyperaccumulator Aluminium exported as wood represented between 74-93% of the total accumulated, so large amounts element was taken out of the planting site during harvest. Nitrogen and K also had high percentages accumulation. Thus, the management of this system should pay special attention to the dynamics three nutrients.